2020
DOI: 10.1016/j.str.2019.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Mg2+-ATP Sensing in CNNM, a Putative Magnesium Transporter

Abstract: Highlights d Structural and functional studies of CNNM, a putative Mg 2+ transporter in human d Crystal structures of cytosolic fragments in open and closed conformations d Tight correlation between Mg 2+ -ATP binding and CBS-pair domain dimerization d Mg 2+ efflux is regulated by conformational changes associated with Mg 2+ -ATP binding

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(70 citation statements)
references
References 55 publications
2
65
2
1
Order By: Relevance
“…Only ADP exhibited a very weak effect on the FRET intensity, altering the intensity by 9.6%. Our result indicates that the interaction between CNNM3 and PRL2 is not regulated by the Mg-ATP complex, whereas a recent study indicated that the Mg-ATP complex is sensed by CNNM 8 .
Figure 5 Effect of divalent cations and nucleotides on the FRET intensities.
…”
Section: Resultscontrasting
confidence: 80%
“…Only ADP exhibited a very weak effect on the FRET intensity, altering the intensity by 9.6%. Our result indicates that the interaction between CNNM3 and PRL2 is not regulated by the Mg-ATP complex, whereas a recent study indicated that the Mg-ATP complex is sensed by CNNM 8 .
Figure 5 Effect of divalent cations and nucleotides on the FRET intensities.
…”
Section: Resultscontrasting
confidence: 80%
“…The Cystathionine-β-synthase (CBS)-pair domain divalent metal cation transport mediators (CNNMs) have been described to be involved in maintaining Mg2+ homeostasis. This family includes four proteins (CNNM1, CNNM2, CNNM3 and CNNM4) [6]. Among these, the CNNM2 protein, that was described in 2003 [7], is ubiquitously expressed, although mostly at the basolateral membrane in both the thick ascending limb of the Henle's loop, and the distal collecting tubule within the kidney where it is involved in Mg2+ reabsorption [8].…”
Section: Introductionmentioning
confidence: 99%
“…The exact mechanism by which these proteins facilitate the passing of Mg2+ through the cell membranes has been widely discussed [10,11]. These proteins could be themselves Mg2+ transporters [6,10] or regulate other proteins that transport Mg2+ [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations